Simultaneous determination of epalrestat and puerarin in rat plasma by UHPLC–MS/MS: Application to their pharmacokinetic interaction study. (19th October 2016) - Sun, Hong; Bo, Yunhai; Zhang, Mingjie; Wu, Xiao; Zhou, Mingyang; Zhao, Longshan; Xiong, Zhili
Abstract: In the present study, a simple, rapid and reliable ultrahigh‐performance liquid chromatography–tandem mass spectrometric (UHPLC–MS/MS) method was developed and validated to determine simultaneously epalrestat (EPA) and puerarin (PUE) in rat plasma for evaluation of the pharmacokinetic interaction of these two drugs. Both the analytes and glipizide (internal standard, IS) were extracted using a protein precipitation method. The separation was performed on a C18 reversed phase column using acetonitrile and 5 mmol/L ammonium acetate in water as the mobile phase with a gradient elution program. The analytes, including IS, were quantified with multiple reaction monitoring under negative ionization mode. The optimized mass transition ion pairs ( m / z ) were 318.1 → 274.0 for EPA, 415.1 → 266.9 for PUE and 444.2 → 166.9 for IS. The linear calibration curves for EPA and PUE were obtained in the concentration ranges of 10–4167 and 20–8333 ng/mL, respectively ( r > 0.99). The current method was successfully applied for the pharmacokinetic interaction study in rats following administration of EPA and PUE alone or co‐administration (EPA 15 mg/kg, oral; PUE 30 mg/kg, intravenous). The results showed that the combination of EPA and PUE could increase t 1/2 of EPA and reduce T max of EPA. These changes indicated that EPA and PUE might cause drug–drug interactions when co‐administrated.